Media and Islamism in Post-New Order Indonesia: The Case of Sabili - Rijal, Syamsul (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2005)
This article examines the Islamist issues presented by the Sabili magazine in post-New Order Indonesia from 1998 to 2004. This study is mainly inspired by the resurgence of Islamism as a consequence of political liberalization that resulted from the fall of Soeharto in May 1998. The press freedom permitted by president Habibie has given Islamic media such as the Sabili magazine the opportunity to operate relatively freely, unlike the restrictions faced during the New Order era. Sabili magazine, as the object of this study, has for sometime been a popular Islamic magazine among Muslim readers in Indonesia.DOI: 10.15408/sdi.v12i3.582